Pomegranate seed extract attenuates chemotherapy-induced liver damage in an experimental model of rabbits. - Yildirim, N. C.; Kandemir, F. M.; Ceribasi, S.; Ozkaraca, M.; Benzer, F. (Cellular and Molecular Biology, 2013)
The aim of this study was to determine whether antioxidant pomegranate seed extract (PSE) has a preventive effect on cisplatin-induced hepatotoxicity. Rabbits were divided into 3 groups (n=6):1-Control group (0.9 % saline. i.p) 2-Cisplatin group (a single dose of cisplatin (5 mg/kg, i.p) 3- A single dose of cisplatin (5 mg/kg, i.p) + PSE (250 mg/kg/day, i.p) for 6 consecutive days before and 6 consecutive days after a single intraperitoneal dose of 5 mg/kg body weight cisplatin. Liver function enzymes and malondialdehyde (MDA) levels were found significantly higher in cisplatin group compared to control. Liver catalase (CAT) and glutathione peroxidase (GSH-PX) activities decreased with cisplatin treatment but glutathione (GSH) level was increased. In cisplatin + PSE group, liver function enzyme activities and tissue MDA levels were found lower than cisplatin group. PSE ameliorated cisplatin-induced pathological changes. As a result it was demonstrated that PSE has protective effects against cisplatin hepatotoxicity in rabbit.